Sex-based differences in endurance exercise muscle metabolism: impact on exercise and nutritional strategies to optimize health and performance in women - Devries, M. C. (Experimental Physiology, 2015)
Sex-based differences in substrate metabolism during moderate-intensity endurance exercise (END) have been well established. Specifically, during END of the same intensity women have a lower respiratory exchange ratio (RER) as compared with men, indicative of a lesser reliance on carbohydrate (CHO) oxidation to support exercise fuel needs. In fact, as compared with men, women show a lesser reliance on both liver and muscle glycogen during END. Sex-based differences in intramyocellular lipid (IMCL) utilization during END are controversial. However, women have a greater depot of IMCL available to support END fuel needs and a greater percentage of IMCL in contact with mitochondria following a bout of END as compared with men, suggestive of a greater capacity to utilize IMCL. These sex-based differences in metabolism during END are known to be mediated by estrogen. Despite the well-recognized sexual dimorphisms in END substrate metabolism, there is a paucity of research examining the effects of exercise and nutritional regimes aimed to enhance performance and/or health in women. Furthermore, the evidence that does exist is suggestive of discordance in the effectiveness of nutritional and exercise regimes between the sexes. The focus of this review will be to provide an overview of the well-established sex-based differences in metabolism during END and how they relate to the physiological responses to nutritional and exercise strategies intended to improve exercise performance and/or health.